2018
DOI: 10.1016/j.jpainsymman.2017.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Czech Version of the Patient Dignity Inventory: Translation and Validation in Incurable Patients

Abstract: The results from the study support the reliability of the PDI-CZ and its future use in patients with incurable cancer and noncancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 25 publications
1
28
0
Order By: Relevance
“…The respondents saw the research as an opportunity to talk to someone about their illness and other important aspects of life. This confirms that the PDI-CZ is not only a measurement tool, but can also be used as an intervention because it facilitates professional communication with the geriatric inpatient with in LTC (Kisvetrová et al, 2018).…”
Section: Geriatric Depression Scale (Gds-15supporting
confidence: 65%
See 1 more Smart Citation
“…The respondents saw the research as an opportunity to talk to someone about their illness and other important aspects of life. This confirms that the PDI-CZ is not only a measurement tool, but can also be used as an intervention because it facilitates professional communication with the geriatric inpatient with in LTC (Kisvetrová et al, 2018).…”
Section: Geriatric Depression Scale (Gds-15supporting
confidence: 65%
“…The intensity tells us how this is perceived by the respondent as a problem or cause for concern in relation to a threat to perceived dignity (higher score presents greater threat of dignity) ( Chochinov et al, 2008 ). In our study, we used a validated Czech version (PDI-CZ; Kisvetrová et al, 2018 ), which was validated for the needs of Czech nursing practice. PDI-CZ has high reliability (α = .92) and contains four domains.…”
Section: Methodsmentioning
confidence: 99%
“…However, the next step is psychometric testing, such as factor analysis and test-retest of the PDI-SWE in a larger group of patients. PDI has been translated and validated in different countries with satisfactory psychometric results (Albers et al, 2011;Ripamonti et al, 2012;Sautier et al, 2014;Rullan et al, 2015;Parpa et al, 2017;Kisvetrova et al, 2018). In a recent review focusing on identifying PROMs suitable for use in palliative care for clinical practice and/or research purposes, the PDI received the highest score (Johnston et al, 2017a).…”
Section: Discussionmentioning
confidence: 99%
“…As a screening tool, the PDI has been shown to be beneficial, ensuring that issues causing dignity-related distress can be identified in a holistic way (Chochinov et al, 2012). The PDI has been adapted to, and validated for use in, diverse countries, including the Netherlands (Albers et al, 2011), Czech Republic (Kisvetrova et al, 2018), Italy (Ripamonti et al, 2012), Germany (Sautier et al, 2014), Greece (Parpa et al, 2017), and Spain (Rullan et al, 2015), but not Sweden.…”
mentioning
confidence: 99%
“…There was also proven a significant correlation among all the factors (subscales). the individual correlations are shown in table 14. the study has shown that the PDi-CZ Czech version has good psychometric features and is therefore appropriate to use also in international studies (Kisvetrová et al, 2018b). in the Czech version of the PDi-CZ, items are divided into four subscales corresponding to the four factors determined based on the result of the factor analysis (Kisvetrová et al, 2018b).…”
Section: C) Reverse Translation To the Original (English) Languagementioning
confidence: 99%